Development of an Andragogy-Based Partnership Supervision System for Madrasah Principals - Rindiani, Ani; Rindanah, Rina; Saepudin, Asep; Yahya, Faridah Hanim (Journal of Nonformal Education, 2026)
Background - Academic supervision is a function of madrasah principals that assists teachers in improving the quality of learning processes and outcomes. However, literature review and a preliminary survey in public madrasahs in Sumedang Regency indicated that supervision remained interrogative, emphasized inspections to identify errors, did not encourage teachers to try new practices, and provided little opportunity for teachers to analyze weaknesses in their teaching.Research Urgency - This article examines an andragogy-based partnership supervision system intended to support a more humane and constructive implementation of academic supervision.Research Objectives - This study aimed to explore the design and implementation of an andragogy-based partnership supervision system, examine the associated learning outcomes, and develop a supervision model.Research Methods - The study used a research and development approach adapted into four stages: introduction, design, development, and dissemination. Qualitative data were collected through observation, interviews, and document analysis, while quantitative data were obtained through questionnaires and a one-group pretest-posttest evaluation.Research Findings - The study produced a system design, documented its implementation, and examined preliminary effectiveness through changes in the knowledge and competence of madrasah principals. The mean academic supervision competency score increased from 18.00 to 51.25, a gain of 33.25 points, reported as approximately 65%.Conclusion and Research Novelty - The andragogy-based partnership supervision system constitutes an innovative product that can serve as a theoretical and practical reference for academic supervision conducted by madrasah principals.